2010
DOI: 10.4102/sajp.v66i2.62
|View full text |Cite
|
Sign up to set email alerts
|

A daily physical activity and diet intervention for individuals with type 2 diabetes mellitus: a randomized controlled trial

Abstract: Urbanisation,  a  sedentary  lifestyle  and  increasing  obesity  due  to westernization and changed eating habits have been identified as independent risk factors for diabetes in the South African population. To establish the effectiveness of a daily walk and diet education intervention program. A randomized controlled trial was performed. The study population consisted of men and women of all races, ages 40 to 65 with Type 2 Diabetes Mellitus (DM) of duration at least one year attending the Steve Biko Diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(30 citation statements)
references
References 5 publications
0
29
0
1
Order By: Relevance
“…The two theories that were used most frequently to explain the intervention were social cognitive theory and self-efficacy theory, which are closely linked. The Health Belief Model, [14][15][16] the Trans Theoretical Model of Behaviour Change, [16][17][18] Social Learning Theory, 15,19 Social Ecological Theory, 20,21 Goals System Theory, 20 Rationale Emotive Theory, 22 and the Skilled Helper Model 23 were also listed as supporting the underlying self-management intervention. There were two diseases, chronic obstructive pulmonary disease and chronic pain, where only 25% of the studies reviewed had a theoretical underpinning for their self-management intervention.…”
Section: Resultsmentioning
confidence: 99%
“…The two theories that were used most frequently to explain the intervention were social cognitive theory and self-efficacy theory, which are closely linked. The Health Belief Model, [14][15][16] the Trans Theoretical Model of Behaviour Change, [16][17][18] Social Learning Theory, 15,19 Social Ecological Theory, 20,21 Goals System Theory, 20 Rationale Emotive Theory, 22 and the Skilled Helper Model 23 were also listed as supporting the underlying self-management intervention. There were two diseases, chronic obstructive pulmonary disease and chronic pain, where only 25% of the studies reviewed had a theoretical underpinning for their self-management intervention.…”
Section: Resultsmentioning
confidence: 99%
“…Among the included studies, five covered all components of DSM, [28][29][30][31][32] and two covered diet therapy, physical activity, medication and avoiding complications. 27,33 One study covered physical activity and dietary intake topics in education, 34 and another covered nutritional therapy education. 35 Six studies were delivered using a group approach 27,29,[32][33][34][35] while three were delivered individually.…”
Section: Intervention Characteristicsmentioning
confidence: 99%
“…27,33 One study covered physical activity and dietary intake topics in education, 34 and another covered nutritional therapy education. 35 Six studies were delivered using a group approach 27,29,[32][33][34][35] while three were delivered individually. 28,30,31 The intervention period ranged from 3 months to 2 years.…”
Section: Intervention Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Between-group comparison did not yield any significant differences in any of the parameters following the 8-week exercise program. In contrast, some previous studies have shown significant improvement in HbA 1c , total cholesterol, high-density lipoprotein, low-density lipoprotein, and triglycerides in patients with type 2 diabetes who engaged in structured physical activities compared with controls, 6 , 10 12 thereby lending credence to the general belief that aerobic exercise is beneficial in the management of patients with type 2 diabetes. The inconsistencies in these studies could be attributed to varying factors ranging from differences in study design to socioeconomic and sociodemographic factors.…”
Section: Discussionmentioning
confidence: 83%